Atomic Layer Deposition of ZnO on InP Quantum Dot Films for Charge Separation, Stabilization, and Solar Cell Formation. Issue 4 (15th January 2020) - Crisp, Ryan W.; Hashemi, Fatemeh S. M.; Alkemade, Jordi; Kirkwood, Nicholas; Grimaldi, Gianluca; Kinge, Sachin; Siebbeles, Laurens D. A.; van Ommen, J. Ruud; Houtepen, Arjan J.
Abstract: To improve the stability and carrier mobility of quantum dot (QD) optoelectronic devices, encapsulation or pore infilling processes are advantageous. Atomic layer deposition (ALD) is an ideal technique to infill and overcoat QD films, as it provides excellent control over film growth at the sub‐nanometer scale and results in conformal coatings with mild processing conditions. Different thicknesses of crystalline ZnO films deposited on InP QD films are studied with spectrophotometry and time‐resolved microwave conductivity measurements. High carrier mobilities of 4 cm 2 (V s) −1 and charge separation between the QDs and ZnO are observed. Furthermore, the results confirm that the stability of QD thin films is strongly improved when the inorganic ALD coating is applied. Finally, proof‐of‐concept photovoltaic devices of InP QD films are demonstrated with an ALD‐grown ZnO electron extraction layer. Abstract : The technique of atomic layer deposition (ALD) provides an ideal method for fabricating designer materials. The authors develop a facile ambient pressure variant of ALD to coat and in‐fill films of quantum dots. This intimate contact between an electron accepting material affords enhanced charge transport, molecular‐scale encapsulation, and rectifying junction formation for solar cells.